Analysis of carbon nanotube device physics - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (Science Publishing Group, 2014)

(untitled)
In this paper, the device physics of carbon nanotubes is analyzed depend on the graphene structure. The analysis is done to calculate energy dispersion relation, effective mass and intrinsic carrier concentration of graphene to establish different carbon nanotubes. Diameters with different chiral vector (n, m) of carbon nanotubes vary the electronics properties of graphene. Different chiral vector of a graphene allows designing carbon nanotube (CNT) for different types of appliance, which can be achieved from the analyzed carrier concentration calculation. This investigation will helpful for further designing of CNT-based nano device.